THE USE OF CHLOROSULFONIC ACID ON SULFONATION OF cPTFE FILM GRAFTED STYRENE FOR PROTON EXCHANGE MEMBRANE - Yohan Yohan (Universitas Gadjah Mada, 2007)
Sulfonation of g-ray iradiated and styrene-grafted crosslinked polytetrafluoro ethylene film (cPTFE-g-S film) have been done. The aim of the research was to make hydrophyl membrane as proton exchange membrane fuel cell. Sulfonation was prepared by using chlorosulfonic acid in chloroethane under various conditions. The impact of the percentage of grafting, the concentration of chlorosulfonic acid, the reaction time,and the reaction temperature on the properties of sulfonated film were examined. The results show that sulfonation of surface-grafted films was incomplete at room temperature. Increasing concentration of chlorosulfonic acid and reaction temperature accelerate the reaction but they also favor side reactions. These lead to the decrease of the ion-exchange capacity, water uptake, and proton conductivity but the increase of the resistance to oxidation in a perhydrol solution. The resulted cPTFE-g-SS membraneis stabile in a H2O2 30% solution for 20 h.